Metrics to evaluate R, D & E - Hauser, John R.
John R. Hauser and Florian Zettelmeyer summarize the findings of a study on metrics and how their selection affects not only research decisions and efforts but the researchers themselves.
Select the right metric for each activity and you encourage the right decisions and actions by scientists, engineers and managers. A study provides guidelines.
Metrics affect research decisions, research efforts, and the researchers themselves. From a review of the literature, interviews at ten research-intensive organizations,and formal mathematical analyses, the authors conclude that the best metrics depend upon the goals of the R, D&E activity as they vary from applied projects to competency-building programs to basic research explorations. For applied projects, market outcome metrics (sales, customer satisfaction, margins, profit) are relevant if they are adjusted via corporate subsidies to account for short-termism, risk aversion, scope and options thinking. The magnitude of the subsidy should vary by project according to a well-defined formula.